(untitled) - Frommer, Harvey (Hoboken, N.J., 2008)
This is the second book on the New York Yankees entitled Five O'Clock Lightning. The first came out a few years ago and was written by former Yankee Tommy Henrich and Bill Gilbert. This new version on the 1927 Yankees provides us with an introduction to each of the players on the roster including Manager Miller Huggins and batboy Eddie Bennett.
Keywords: Baseball,Baseball players,Bóng chày,Cầu thủ bóng chày; History,Lịch sử; New York (State),New York,United States,New York,Hoa Kỳ